The Grammar Translation Method, The Direct Method, and The Audio-Lingual Method - Risnawati Djauhar (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2021)
This article briefly presents the characteristics of different teaching methods, namely the grammar translation method, the direct method, and the audio-lingual method. Many authors have discussed each method separately and in this brief communication I will present the characteristics of each comparable method. The significance of the discussion in this article, theoretically and practically, can help teachers decide which method will work best for them and their students. By having knowledge about the characteristics of each method, teachers can make optimal use of the method they choose so that learning outcomes can be achieved optimally.